The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5812/jnms-138604
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Maternal Hypothyroidism and the Incidence of Congenital Hypothyroidism in Infants: A Cross-Sectional Study

Roya Oboodi,
Bahareh Fallah,
Reza Bahrami
et al.

Abstract: Background: Congenital hypothyroidism (CH) can influence neonates’ neurodevelopment. There are controversies on the cause of infantile hypothyroidism and its relationship with maternal hypothyroidism. Objectives: This study aimed to investigate the relationship between maternal hypothyroidism and the incidence of CH. Methods: This cross-sectional study was conducted on 712 newborns with hypothyroidism born in Fars province, Iran, between 2018 and 2020, identified through the national screening program for gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In this study, family history has a statistically significant relationship with congenital hypothyroidism, especially the history of the mothers of newborns. Like most studies inside and outside the country (40,47,6,49,48).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, family history has a statistically significant relationship with congenital hypothyroidism, especially the history of the mothers of newborns. Like most studies inside and outside the country (40,47,6,49,48).…”
Section: Discussionmentioning
confidence: 98%
“…A study in East Azarbaijan province also revealed that the age of delivery had a statistically significant relationship with congenital hypothyroidism. In another study that was conducted in Hamadan, in addition to gestational age, anemia, and maternal goiter, Zeman type, The most important risk factors were maternal hypothyroidism and showed a significant relationship with CH (41,49).…”
Section: Discussionmentioning
confidence: 98%